Qualidade ambiental em áreas agrícolas da caatinga potiguar usando entomofauna edáfica - Cruz, Joiza Maria (Universidade Federal Rural do Semi-Árido, 2014)
Agriculture is one of the human activities that degrade the environment more.Thus, this study aimed to analyze, as edaphic insect fauna is related to the environmental quality of the area irrigated Farm Sabia, and its surroundings.The study took place from 1 August to 22 August 2013.The insects were collected weekly by pitfall traps, unattractive, composed of 60 plastic containers with a capacity of 350 mL, 15 disposed in each of the four randomly chosen areas, distant from each other 10 meters.8,590 insects in 37 families and 08 orders, which were collected 503, 889, 2,479 and 4,719 in the former areas, intermediate, and native home, respectively, were found in three collections. The bioindicators families collected were Formicidae, Carabidae, Scarabaeidae, Staphylinidae. The diversity indices of Shannon-Wiener were 1.91, 1.38, 1.35 and 1.23 for the former, native, resting and intermediate areas respectively. And for Equitability evenness were respectively 0.61, 0.43, 0.42 and 0.41 for the old , intermediate, native and resting areas. Already dominance Simpson were respectively 0.73, 0.57, 0.54 and 0.48 for old, native, intermediate and resting areas
Assessment of environmental quality using in agricultural areas entomofauna edaphic of the caatinga
Keywords: Agriculture; Caatinga - RN; Insects; Edaphic insect fauna; Environmental quality; Agricultura; Caatinga potiguar; Insetos; Entomofauna edáfica; Qualidade ambiental; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE